Conditional immune toxicity rate in patients with metastatic renal and urothelial cancer treated with immune checkpoint inhibitors. Issue 1 (30th March 2020) - Nuzzo, Pier Vitale; Pond, Gregory R; Abou Alaiwi, Sarah; Nassar, Amin H; Flippot, Ronan; Curran, Catherine; Kilbridge, Kerry L; Wei, Xiao X; McGregor, Bradley A; Choueiri, Toni; Harshman, Lauren C; Sonpavde, Guru
Abstract : Background: Immune checkpoint inhibitors (ICIs) are associated with immune-related adverse events (irAEs). Although the incidence and prevalence of irAEs have been well characterized in the literature, less is known about the cumulative incidence rate of irAEs. We studied the cumulative incidence of irAEs, defined as the probability of irAE occurrence over time and the risk factors for irAE development in metastatic urothelial carcinoma (mUC) and renal cell carcinoma (mRCC) patients treated with ICIs. Methods: We identified a cohort of patients who received ICIs for mUC and mRCC. irAEs were classified using Common Terminology Criteria for Adverse Event (CTCAE) V.5.0 guidelines. The monthly incidence of irAEs over time was reported after landmark duration of therapy. Cumulative incidence of irAEs was calculated to evaluate the time to the first occurrence of an irAE accounting for the competing risk of death. Prognostic factors for irAE were assessed using the Fine and Gray method. Results: A total of 470 patients were treated with ICIs between July 2013 and October 2018 (mUC: 199 (42.3%); mRCC: 271 (57.7%)). 341 (72.6%) patients received monotherapy, 86 (18.3%) received ICIs in combination with targeted therapies, and 43 (9.2%) received dual ICI therapy. Overall, 186 patients (39.5%) experienced an irAE at any time point. Common irAEs included hypothyroidism (n=42, 22.6%), rush and pruritus (n=36, 19.4%), diarrhea/colitis (n=35, 18.8%), transaminitis (n=32, 17.2%), and pneumonitis (n=14, 7.5%). Monthly incidence rates decreased over time; however, 17 of 109 (15.6%, 95% CI: 9.4% to 23.8%) experienced their first irAE at least 1 year after treatment initiation. No differences in cumulative incidence were observed based on cancer type, agent, or irAE grade. On multivariable analysis, combined ICI therapy with another ICI or with targeted therapy (p<0.001), first-line ICI therapy (p=0.011), and PD-1 inhibitor therapy (p=0.007) were all significantly associated with irAE development. Conclusions: This study quantitates the incidence of developing irAEs due to ICI conditioned on time elapsed without irAE development. Although the monthly incidence of irAEs decreased over time on therapy, patients can still develop delayed irAEs beyond ICI discontinuation, and thus, continuous vigilant monitoring is warranted.